2019
DOI: 10.12669/pjms.35.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment rate of true dorsogluteal intramuscular drug injection using ultrasonography

Abstract: Objective: Medications are generally administered by either the enteric or parenteral route. With parenteral administration, intramuscular (IM) is the preferred approach because it increases the bioavailability of the drug, acts more quickly than the enteric route. The aim of this study was to determine the rate of true dorsogluteal intramuscular drug injection and to determine the causes for application failures in practice by ultrasonography (US). Methods: The study was conducted from May 1 to May 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Intramuscular (IM) injections are a vehicle to dispense medications such as antibiotics, vitamins, infertility drugs, allergy medications and antipsychotic medications. These and other medications need to be administered IM into large gluteal muscles to allow for better absorption of high‐volume medication (Ozen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intramuscular (IM) injections are a vehicle to dispense medications such as antibiotics, vitamins, infertility drugs, allergy medications and antipsychotic medications. These and other medications need to be administered IM into large gluteal muscles to allow for better absorption of high‐volume medication (Ozen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, studies have shown that numerous dorsogluteal IM injections intended for intramuscular placement were instead injected into the subcutaneous adipose tissue (SAT) due to needle lengths that were too short to reach muscle tissue (Chan et al, 2006; Cockshott et al, 1982; Ozen et al, 2019). Excessive adipose tissue may lead to higher risk of injections placed into subcutaneous tissue instead of muscle, especially in women (Ajana et al, 2008; Bhalla et al, 2013; Chan et al, 2006; Dayananda et al, 2014; Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Safe and reliable outcomes from these injections cannot be thoroughly evaluated clinically, however, studies using paraclinical diagnostic techniques, including MRI, Computerised Tomography (CT) scan, and Ultrasound to evaluate injection success have reported success rates of 32%–52% (Ozen et al, 2019; Soliman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The gluteal muscles are a common site for the administration of IM medications (Ozen et al, 2019) and nurses have expressed a preference for utilising the dorsogluteal site rather than the ventrogluteal site (Kara et al, 2015). In comparing patient safety, it has been suggested that injections into the ventrogluteal site are safer for the patient due to a sufficient distance from the sciatic nerve, but when accurately identified, an injection into the dorsogluteal area carries no greater risk (Larkin, Ashcroft, Elgellaie, et al, 2017; Larkin, Ashcroft, Hickey, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%